2018
DOI: 10.18203/2394-6040.ijcmph20183420
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sleep habits among medical and non-medical students in Saifai, Etawah

Abstract: Background: Good quality sleep and adequate amount of sleep are important in order to have better cognitive performance, academic performance and avoid health problems and psychiatric disorders. Sleep disturbance is a distressing and disabling condition that affects many people, and can affect on quality of work and education of students. Thus the aim of the study is to assess and compare the sleep habits of medical and non-medical students in Etawah city.Methods: A cross-sectional study was carried out among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…The results for the sleep duration component revealed that the maximum (34.3%) participants were sleeping for 5-6 hours per night while 28% of participants were sleeping for less than 5 hours. Similarly, daily sleeping hours of 4-6 hours were reported by 69.38%[ 19 ] and 70.9%[ 20 ] participants in other studies. Also, 68.0% of the participants reported sleeping for 6-7 h per night in another study.…”
Section: Discussionsupporting
confidence: 58%
“…The results for the sleep duration component revealed that the maximum (34.3%) participants were sleeping for 5-6 hours per night while 28% of participants were sleeping for less than 5 hours. Similarly, daily sleeping hours of 4-6 hours were reported by 69.38%[ 19 ] and 70.9%[ 20 ] participants in other studies. Also, 68.0% of the participants reported sleeping for 6-7 h per night in another study.…”
Section: Discussionsupporting
confidence: 58%
“…Students reporting sleep disorders such as insomnia were more likely to use sedative drugs. 46 , 47 In this study, sedative drug use was more common among students who slept for less than 4 hours per day (38.46% versus 9.09%) (AOR (95% CI), 9.989 (4.646–14.188) P = 0.001) than those who slept for greater than 8 hours per day, and this association strongly supported by a study conducted in Saudi university AOR (95% CI), 1.743 (1.122–2.705 P = 0.0013). In the current study, sedative drug use was less common among students who did not report sleeping disorders than those who reported sleeping disorders (2.98% versus 28.30%) (AOR (95% CI), 0.131 (0.029–0.599) P = 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…personal quality of life and occupational performance negatively. 20,23 The correlation of demographic characteristics with sleep quality in those studying medicine is a point of controversy. For instance, there are studies in agreement with ours regarding the independency of sleep disturbances from sex, 24 while Akhlaghi and co-workers represented worse conditions in girls in Iran 25 that was consistent with the results of another study in Pakistan, 26 a fact that probably may have occurred because of the boys better ability to adapt to hard studying and stressful medical conditions.…”
Section: Sleep Disturbances and Gastroesophageal Refluxmentioning
confidence: 99%